Improving Students’ Learning Activeness and Achievement through the Two Stay Two Stray Learning Model Integrated with Group Guidance - Novrina Ika (Journal of Teaching and Education, 2025)
Learning activeness and academic achievement are essential indicators of successful instructional processes. However, many junior high school students still demonstrate low participation and limited engagement during classroom learning activities, which negatively affects their learning outcomes. This study aims to improve students’ learning activeness and academic achievement through the implementation of the Two Stay Two Stray (TSTS) learning model integrated with group guidance. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were students of class VIII at SMP Negeri 29 Rumbia in the academic year 2024/2025. Data were collected through classroom observations, learning achievement tests, and documentation. Quantitative data were analyzed using percentage analysis, while qualitative data were analyzed descriptively to support the quantitative findings. The results revealed a significant improvement in students’ learning activeness and academic achievement. Students’ activeness increased from 59.67 in Cycle I to 84.94 in Cycle II. In addition, students’ learning achievement improved from an average score of 67.18 in Cycle I to 81.32 in Cycle II. The percentage of students achieving mastery learning also increased from 54.84% to 70.97%. These findings indicate that the integration of the Two Stay Two Stray learning model with group guidance effectively enhances students’ engagement and learning outcomes.  Therefore, it can be concluded that the application of cooperative learning models supported by group guidance is an effective strategy to improve students’ learning activeness and academic achievement. This approach is recommended for teachers seeking to create a more interactive, student-centered, and meaningful learning environment.